Miocene Toothed Whales (Cetacea, Odontoceti) from the Dniester Valley: The First Record of Miocene Sperm Whales (Physeteroidea) from the Eastern Europe - Gol’din, P.E.; Marareskul, V.A. (Вестник зоологии, 2013)
Isolated odontocete teeth were found in two Miocene sites in the Dniester River valley. Cetaceans from the both sites possibly represent unknown taxa. One of them is a stem physeteroid, the most similar to Scaldicetus caretti and Early Miocene taxa; another one can be a stem physeteroid or a large stem delphinoid.